2018
DOI: 10.1158/0008-5472.can-18-0155
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Specific and General Nutritional Scores and Cancer Risk: Results from the Prospective NutriNet-Santé Cohort

Abstract: Several national and international authorities have proposed nutritional and lifestyle recommendations with the aim of improving health of the general population. Scores of adherence to these recommendations can be calculated at the individual level. Here, we investigated the associations between four nutritional scores and overall, breast, prostate, and colorectal cancer risk in a large prospective population-based cohort: the cancer-specific World Cancer Research Fund/American Institute for Cancer Research (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
66
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 39 publications
6
66
1
3
Order By: Relevance
“…After publication of the second expert report, numerous studies developed a composite score to measure adherence to the WCRF/AICR cancer prevention guidelines, which hereafter is called an adherence score. These studies reported a link between a higher adherence score and better quality of life, lower morbidity, and lower mortality from several types of cancer, including CRC …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…After publication of the second expert report, numerous studies developed a composite score to measure adherence to the WCRF/AICR cancer prevention guidelines, which hereafter is called an adherence score. These studies reported a link between a higher adherence score and better quality of life, lower morbidity, and lower mortality from several types of cancer, including CRC …”
Section: Introductionmentioning
confidence: 98%
“…These studies reported a link between a higher adherence score and better quality of life, lower morbidity, and lower mortality from several types of cancer, including CRC. [1][2][3][6][7][8][11][12][13][14][15][16][17][18][19][20][21] Among studies that showed an inverse association between a higher adherence score and lower CRC incidence were the European Prospective Investigation Into Cancer and Nutrition (EPIC) cohort 2 and the Vitamins and Lifestyle (VITAL) cohort. These studies found a stronger association in men than women 3 ; however, they included predominantly white participants.…”
Section: Introductionmentioning
confidence: 99%
“…Based on studies evaluating the associations between lifestyle factors and cancer risk, the objective of these recommendations was to empower individuals to take actions to lead cancer‐free lives. Many studies conducted in Western populations have shown that adopting a favorable lifestyle pattern was associated with lower risks of overall and site‐specific cancers . For example, the European Prospective Investigation into Cancer and Nutrition (EPIC) study found that adherence to the 2007 WCRF/AICR guidelines was associated with reduced risks of overall or site‐specific cancers .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The World Cancer Research Fund International (WCRF) and American Institute for Cancer Research (AICR) have jointly issued and updated healthy lifestyle recommendations for cancer prevention since 1997. 5 Based on studies evaluating the associations between lifestyle factors and cancer risk, the objective of these recommendations was to empower individuals to take actions to lead cancer-free lives. Many studies conducted in Western populations have shown that adopting a favorable lifestyle pattern was associated with lower risks of overall and site-specific cancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation